EFFECT OF CARBON SOURCES AND EXPLANTS ON IN VITRO MULTIPLICATION OF POTATO - Venkatasalam, E P; Singh, B P; Singh, K K; Latawa, Jyoti; Sharma, Shilpa; Sood, Richa; Thakur, Vandana (Potato Journal, 2013)
In order to reduce the in vitro production cost, a study was conducted to evaluate the efficacy of two carbon sources viz., sucrose and commercial sugar on in vitro multiplication rate of fifteen potato cultivars using two types of explants. Significant response of carbon sources, explants and cultivars was observed on different morphological characters of in vitro plantlets. Sucrose as a carbon source resulted in a significant increase in the number of nodes in Kufri Badshah, Kufri Chipsona-3, Kufri Giriraj, Kufri Himsona and Kufri Pukhraj which ultimately influences the multiplication rate. However, number of nodes was not affected significantly with the source of carbon in a majority of other potato cultivars viz., Kufri Anand, Kufri Bahar, Kufri Chandramukhi, Kufri Chipsona-1, Kufri Girdhari, Kufri Himalini, Kufri Kanchan, Kufri Lauvkar, Kufri Pushkar and Kufri Sutlej. Use of double node cuttings as explant source resulted in a significant increase in the number of nodes in Kufri Himalini and Kufri Himsona only, whereas, in all other cultivars both the explants viz., double as well as single node performed equally. Thus, in the majority of potato cultivars commercial sugar can be used successfully for reducing the cost of production of in vitro potato plantlets and single node as explants for increasing the multiplication rate without affecting the quality.